Posterior mediastinal extralobar pulmonary sequestration in a neonate with pulmonary artery supply: a case report - Mao, Kaiyi; Wang, Leibo; Mao, Yuchen; Shang, Xianhui; Zhou, Guangxu; Zhao, Peng; Wang, Cao; Ma, Hong (Frontiers in Medicine, 2024)
This paper reports a rare case of extralobar pulmonary sequestration in the posterior mediastinum of a neonate with arterial supply from the pulmonary artery. A 3-day-old male neonate was diagnosed with type II congenital pulmonary airway malformation after prenatal color Doppler ultrasonography showed a lesion with blood supply from the pulmonary artery in the left lung. Post-birth chest computed tomography(CT) showed that the lesion was located in the posterior mediastinum with low density change, mild stripe enhancement after contrast, and no obvious blood supply vessels. A neurogenic tumor was considered for the preoperative diagnosis. The mass was removed by video-assisted thoracoscopic surgery. During the surgery, the mass was observed to be a dark red solid lump with a feeding vessel originating from the pulmonary artery. The postoperative histopathological diagnosis was extralobar pulmonary sequestration. Combined with the preoperative imaging results, it was considered that the nourishing vessels might have intermittent torsion.The patient recovered well after surgery, and no recurrence was observed after 6 months of follow-up. Therefore, the possibility of extralobar pulmonary sequestration cannot be ruled out for posterior mediastinal masses that are not supplied by the descending aorta or without identified feeding vessels.